What's Hot in 2021: Beyond the Science of Reading. Issue 1 (2nd January 2022) - Cassidy, Jack; Grote-Garcia, Stephanie; Ortlieb, Evan
ABSTRACT: Literacy topics fluctuate each year in how much attention they receive in research and practice. The What's Hot in Literacy annual survey asks twenty-five leading experts what literacy topics are currently receiving attention, or are hot, as well as which topics should be hot in the field. The results of these interviews are tallied to identify consensus among the participants. The following three levels are used to report the findings: a) "extremely hot" or "extremely cold" (100% consensus), b) "very hot" or "very cold" (75% consensus), and c) "hot" or "cold" (50% consensus). Items are identified as "should be hot" or "should not be hot" if at least 50% of the respondents agree. The four "very hot" topics for 2021 are digital literacy, dyslexia, phonics/phonemic awareness, and social justice/equity/anti-racism in literacy. Discussion of these topics (and others that were deemed should be hot) and why they may be currently receiving more attention than others in the field is included. Findings can be utilized by both K-12 and higher education professionals alike.